Inclusão laboral da pessoa surda: a relação educação/trabalho - COSTA, Josiane Coelho da (2024)
Many discussions have brought up the issue of Special Education as an essential factor for people with disabilities. However, after this period of their lives, what will these social actors do? Will they live off the charity of others or the State? It is believed that insertion into the job market is also crucial for them to have autonomy and more independence. Therefore, education and the job market are intertwined and can influence the training and performance of people with disabilities in the exercise of their social functions. In this sense, this research presents the scenario of labor inclusion of deaf people, seeking to understand the education/work relationship. As a guiding question for this research, we sought to answer: to what extent is the education process an influential aspect in the inclusion of deaf people in the formal job market in São Luís do Maranhão? In order to answer this question, the main objective of this work was to analyze the influence of the educational process on the inclusion of deaf people in the formal job market in São Luís/MA. As specific objectives, we sought to understand the different fields of professional activity of deaf people and their levels of education in São Luís/MA; list the requirements required by companies during the process of admitting deaf people into the formal job market in São Luís/MA; relate the level of education/professional training of these social actors to the factor of insertion in the job market; and, finally, describe the perceptions of research participants regarding the relevance of the level of education and the inclusion of deaf people in the formal job market. The methodology used was, in the first stage, bibliographical, listing the main theorists who deal with educational and labor inclusion, followed by field research with semi-structured interviews in the city of São Luís/MA, with deaf participants, formally linked to federal and private companies, the Federal Public Institution being the Federal University of Maranhão (UFMA) and the National Social Security Institute (INSS) and two private companies in the retail sector; and the respective managers and managers who work directly with deaf employees. The results showed that education strongly influences the inclusion of deaf people in the job market. He also pointed out that access to higher education is a big step towards seeking vacancies in public positions, with better salaries, while an educational process interrupted in high school could allow for more exhaustive jobs in private companies that hire deaf people just to fulfill what they recommend. the quota law. It was possible to notice that deaf candidates, with a higher education level, in federal spheres in the city of São Luís, still represent an insignificant number. On the other hand, there is a strong presence of deaf people with secondary education in private companies, mainly in supermarket chains and retail stores. Regarding the perceptions of deaf people regarding the relevance of education for labor inclusion, everyone expressed this awareness, while managers tried to highlight that it is not just in the context of deafness, ignoring a reality that needs to be discussed with the aim of materializing social inclusion.